Complex Coronary Instent Chronic Total Occlusion Lesions: Oxidative Stress, Inflammation, and Coronary Stent Lengths. (15th April 2021) - Li, Xia; Guo, Dianxuan; Chen, Ying; Hu, Youdong; Zhang, Fenglin
Abstract : The oxidative stress and inflammation played the key roles in the development of atherosclerotic coronary plaques. However, the relationships between pro/antioxidant, pro/anti-inflammatory status, and complex coronary instent chronic total occlusion lesions were not clear in the elderly patients with very long stent implantations. We tried to evaluate the roles of pro/antioxidant and pro/anti-inflammatory biomarkers in the diagnosis of complex reocclusion lesions in elderly patients after coronary stenting. We evaluated the expression levels of acrolein (ACR), malondialdehyde (MDA), high sensitivity C-reactive protein (hs-CRP), tumor necrosis factor- α (TNF- α ), superoxide dismutase 3 (SOD3), paraoxonase-1 (PON-1), endothelial nitric oxide synthase (eNOS), and stromal cell-derived factor-1 α (SDF-1 α ) in the elderly patients with very long stent implantations and complex reocclusion lesions. Levels of ACR, MDA, hs-CRP, and TNF- α were remarkably increased (P < 0.001 ), and levels of SOD3, PON-1, eNOS, and SDF-1 α were decreased significantly (P < 0.001 ) in the elderly patients with very long stents and complex reocclusion lesions. The prooxidant and proinflammatory biomarkers were remarkably increased, as well as antioxidant and anti-inflammatory biomarkers were decreased significantly in the elderly patients with very long stent implantations and complex reocclusion lesions after coronary stenting. In conclusion, these findings indicated that the imbalance between prooxidant/proinflammatory and antioxidant/anti-inflammatory status was associated with complex reocclusion lesions, suggesting that oxidative stress and inflammation played the key roles in progression of complex reocclusion lesions in the elderly patients with very long stent implantations.